Analysis Of The Differences In Running Intervals On Running Speed Of Students At Mts Al Amin Pakis - Arifin Arifin; Wiwik Kusmawati (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to determine the difference in running intervals on running speed in MTs Al Amin Pakis students. The research method is a quasi-experimental method. The sampling technique is simple random sampling. The sample is 20 students of class VIII A as the experimental class and 20 students of class VIII B as the control class. The data collection technique uses tests and non-tests. The instruments are tests and non-test instruments in the form of questionnaires. The data obtained were analyzed using prerequisite tests for normality tests and homogeneity tests. The results of the t-test that have been carried out with the SPSS program, obtained that the t-count value is greater than the t-table value, meaning that there is a significant difference in running intervals on running speed in MTs Al Amin Pakis student.